2023
DOI: 10.3390/jcm12123930
|View full text |Cite
|
Sign up to set email alerts
|

Remimazolam as an Adjunct to General Anesthesia in Children: Adverse Events and Outcomes in a Large Cohort of 418 Cases

Abstract: Remimazolam was first approved in 2020 as a general anesthetic for adults and still does not have pediatric labeling. Our study will be the first pilot program that administers remimazolam as an adjunct to a general endotracheal anesthetic in children. Between August 2020 and December 2022, electronic medical records were collected for all children who received remimazolam during anesthesia. The remimazolam dosing regimen was extrapolated from the adult package insert, with intravenous induction doses of 12 mg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 22 publications
(29 reference statements)
0
7
0
Order By: Relevance
“…The results show that remimazolam has high clearance rates of 15.9 [12.9-18.2] mL/kg/min (median [IQR]), a small volume of distribution of 0.11 [0.08-0.14] L/kg and a short terminal half-life of 67 min. The 4-hour context-sensitive half-time (CSHT) of remimazolam in children is 17 [12][13][14][15][16][17][18][19][20][21] min, which is comparable to that of propofol, indicating that remimazolam has a rapid decay curve 1222 similar to that of propofol. Notably, the weight-corrected pharmacokinetic characteristics of remimazolam in children are similar to data from previous studies in adults.…”
Section: Pharmacokinetics and Pharmacodynamic Characteristics Of Remi...mentioning
confidence: 99%
See 2 more Smart Citations
“…The results show that remimazolam has high clearance rates of 15.9 [12.9-18.2] mL/kg/min (median [IQR]), a small volume of distribution of 0.11 [0.08-0.14] L/kg and a short terminal half-life of 67 min. The 4-hour context-sensitive half-time (CSHT) of remimazolam in children is 17 [12][13][14][15][16][17][18][19][20][21] min, which is comparable to that of propofol, indicating that remimazolam has a rapid decay curve 1222 similar to that of propofol. Notably, the weight-corrected pharmacokinetic characteristics of remimazolam in children are similar to data from previous studies in adults.…”
Section: Pharmacokinetics and Pharmacodynamic Characteristics Of Remi...mentioning
confidence: 99%
“…A cohort study 14 involving 418 children (4.6±4.52 years) (mean±SD) showed that after 109.4±83.1 min intravenous infusion, the mean time of remimazolam (induction dose 12 mg/kg/h, maintenance dose 1–2 mg/kg/h) from ceasing administration to spontaneous eye-opening was 34.3±15.8 min, which was longer than the time in adults (average 19 min). 15 The discrepancy may have been due to differing degrees of sedation in the presence or absence of endotracheal intubation between children and adults in the abovementioned studies.…”
Section: Pharmacokinetics and Pharmacodynamic Characteristics Of Remi...mentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, despite being an effective choice for short-term continuous sedation, particularly for ICU patients postoperatively, it is worth noting that some studies have demonstrated that remimazolam can impact circulation and breathing, which may serve as a limiting factor for its postoperative use [79] [80] [81].…”
Section: Novel Sedativesmentioning
confidence: 99%
“…Given the limited scope of remimazolam’s use in pediatrics, there is an urgent need for detailed examination and dissemination of pediatric experiences with this drug. While our previous work touched upon remimazolam’s application in general anesthesia in a pediatric cohort [ 6 ], specific investigations into its efficacy and safety in pediatric sedation are sparse. This study aims to bridge this knowledge gap by presenting the outcomes of the first-ever pediatric sedation program using remimazolam, with dosages extrapolated based on approved adult labeling.…”
Section: Introductionmentioning
confidence: 99%